INTERAKSI SOSIAL DALAM MEMBANGUN TOLERANSI ANTAR UMAT BERAGAMA DI DESA BOWOMBARU KABUPATEN TALAUD - Frans Taufik Tumuatja; Zoni Singal; Yoseph Santie (Labor Program Studi Pendidikan Sosiologi, 2021)
The problem in this research is to see about social interaction in building tolerance among religious people in Bowombaru Village, East Melonguane District, Talaud Islands Regency. by using qualitative research methods and data collection techniques, namely interviews and observations so that the results of the research found are Interreligious interactions that have existed for so long in Bowombaru village because people who live side by side are not due to different religious factors but from culture because people who are Muslim are immigrant community from Sangihe who moved and settled in Bowombaru village but in their daily life they live with a sense of tolerance, mutual respect and according to them one of the things that must be maintained is not to look down on other religions and consider other religions to be the most correct. That is what has been guarded by the two religious communities in Bowombaru village.